Step characteristic interaction and asymmetry during the approach phase in long jump - Theodorou, A. S.; Panoutsakopoulos, V.; Exell, T. A.; Argeitaki, P.; Paradisis, G. P.; Smirniotou, A. (Journal of Sports Sciences, 2017)
The aim of this study was to investigate the relative influence of step length (SL) and step frequency (SF) on step velocity (SV) during the approach run of high-level long jumpers and to quantify the asymmetry of these step characteristics. Spatiotemporal data of the approach run were collected during national competition from 10 long jumpers (age 26.2 ± 4.1 years, height 1.84 ± 0.06 m, mass 72.77 ± 3.23 kg, personal best performance 7.96 ± 0.30 m). Analyses were conducted for total approach, early approach and late approach. For the total approach 4/10 athletes were SF reliant and 6/10 athletes favoured neither characteristic. At the early approach, 3/10 athletes were SF reliant and 7/10 athletes favoured neither. During late approach 2/10 athletes demonstrated SL reliance, 7/10 athletes were SF reliant and 1/10 athletes favoured neither. Four athletes displayed significant asymmetry for SL and three for SF. However, no athletes demonstrated significant asymmetry for SV indicating that the asymmetrical demands of take-off do not have a marked influence on step characteristic asymmetry, probably due to the constraints of the event. Consideration should be given to the potentially conflicting demands between limbs for individual athletes.